EFFECT OF RELATED PARTY TRANSACTION ON FIRM VALUE OF LISTED CONSUMER GOODS IN NIGERIA - Onuku, Ibrahim Isa; Gurama, Zakariyau; Shuaibu, Kabiru (Kashere Journal of Management Sciences, 2025)
Related party transactions (RPTs) are of significant interest and concern to various stakeholders in the global economy. This study examines the impact of related party transactions on the firm value of listed consumer goods companies in Nigeria over an eight year period (2015–2023). The study employed a longitudinal research design and purposive sampling technique to achieve its objective.As of December 31, 2023, there were twenty-one (21) listed consumer goods firms in Nigeria, out of which a sample of fourteen (14) was selected. Data were obtained from annual reports and accounts, and panel data regression analysis was used for data analysis.The findings reveal that RPTs have a positive and significant influence on firm value. Similarly, leverage shows a positive and significant relationship with firm value. However, firm size exhibits a negative and significant effect on firm value. The study recommends that firms and regulators ensure transparency and efficient management of related party transactions to mitigate potential risks while optimizing their positive contributions to firm value.